Multiple faults detection using artificial neural network - Mohd. Kamaruddin Abd. Hamid 416302 (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2004